A Platform Toy for Children with Special Educational Needs - Ferreira, Rosário (2022)
In childhood, play is critical to the successful development of children, and it can be regarded as the most important activity in their daily life, allowing interaction and discovery of the world around them. Consequently, it is important to ensure that this birthright is protected and accessible to every child, including those with special needs. Professionals, such as therapists, are often in a position where they can take advantage of the inclusion of toys in their therapies with children. Although, toys are not alike, and they must be carefully thought to be able to fulfil the child’s needs. This paper presents a proposal and the first validation of an inclusive toy, entitled “HugMe”, developed and designed with special attention for children who have cognitive and motor impairments and continue to be appealing to all children.